Aleksander Bocheński and his political realism: an outline - Ariel Orzełek (Folia Historica Cracoviensia, 2021)
Political realism is not easy to define. The analysis of specific cases may help. In this text, I wonder whether Aleksander Bocheński was a political realist. His journalism has undergone a significant evolution. He was a supporter of the Polish „power state” before 1939, he wanted to collaborate with the nazi Germans during the war years, and after the war he was an apologist for People's Poland and a critic of the Third Polish Republic. My considerations prove, that Bocheński was looking for political realism in his life and oeuvre, not always, however, entering this trend of reflection on politics.